The Level of Students' Instructional Performance in the College of Arts and Sciences in Prince Sattam bin Abdul Aziz University in Wadi Al-Dawasir, Saudi Arabia, in the light of Teacher Test - Jaradat, Hani Mahmood (Journal of Educational and Psychological Sciences, 2019)
This study aims to identify the level of Instructional performance of students at the Faculty of Arts and Sciences in Wadi-AL dwaser, Prince Sattam bin Abdul-Aziz University in the light of the Teacher test (TT) and its relationship with some variables, such as sex, specialization, academic level and grade point average. The study sample included (140) male and female students who have applied to teachers test. To test the hypothesis of the study researcher used the arithmetic mean standard deviation, Pearson correlation coefficient test , t-test and the first-order variance analysis of Kruskal-Walls. The results indicated that: 1. Low level of students' performance on the Teacher test in general. 2. There are statistically significant differences in the average performance of students on the teachers test and parameters depending on the gender. 3. No significant statistical differences in the average performance of students on the teachers test and parameters depending on the specialization and academic level. 4. The existence of the average statistically significant correlation between the performances of students on the Teacher test and the grade point average (GPA). The study included several recommendations, the most important of which is the establishment of a question bank to be followed by the University's Evaluation and Testing Unit, preparing students to test the competencies of teachers and teachers and addressing weaknesses in academic performance through the university's review of its academic programs. One of the most prominent proposals of the study is to study the relationship between the academic performance of students in the test of teacher competencies with other variables such as graduation university, graduation year, different academic departments, personal characteristics of students who are testing.
Keywords: students' teaching performance; teacher competency test; teachers; cumulative average; universities